Database of summer fish fauna sampled in river estuaries in the southern part of the Boso Peninsula, Japan - Itsukushima, Rei (Biodivers Data J, 2021)
BACKGROUND: River estuaries provide various ecosystem services, such as nutrient circulation, climate change mitigation, habitats and coastal defence. Information on the various taxonomic groups is collected from large-scale estuaries; however, few studies have focused on river estuaries of small and medium-sized rivers. In particular, information on river estuaries in peninsulas and islands with complex marine environments is lacking. NEW INFORMATION: This paper provides basic information on summer fish fauna in the southern part of the Boso Peninsula, Japan. The Boso Peninsula is located at the northernmost point of where the warm current (Kuroshio) reaches and is considered to have highly endemic fish fauna. In total, 28 families, 51 species and 2,908 individuals were collected from the 27 river estuaries. The data are all accessible from the document “database_fish_estuary_boso (http://ipt.pensoft.net/manage/resource.do?r=database_fish_estuary_boso)”. Further, Sicyopterus japonicus and Microphis brachyurus, which appear in estuaries that are influenced by the Kuroshio, were confirmed. However, these species were confirmed in few of the rivers studied, highlighting the importance of habitat conservation.